2019
DOI: 10.1177/0272431618824745
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Moral Disengagement and Their Associations With Indirect Bullying, Direct Bullying, and Pro-Aggressive Bystander Behavior

Abstract: This study examined the links between seven specific mechanisms of moral disengagement and indirect bullying, direct bullying, and pro-aggressive bystander behavior. In addition, the moderating role of gender on these associations was examined. Participants were 317 Swedish students in Grades 4 to 8 ([Formula: see text], SD = 1.35; 62% girls). Multivariate multiple regression analyses showed that indirect bullying was predicted by gender and victim attribution. Direct bullying was predicted by moral justificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 55 publications
3
82
2
5
Order By: Relevance
“…An 11-item self-report scale (Bjärehed, Thornberg, Wänström, & Gini, 2019) was used to measure bullying perpetration without using the word "bullying" to avoid the risks of under-reporting (i.e., social desirability bias based on the socially negative loading of the word) and misconception (i.e., incomplete, inaccurate or misleading personal conceptions of bullying). Instead of mentioning the word "bullying" and providing an a priori definition of bullying, the students were asked, "Think about the past three months: How often have you done the following things towards someone who is weaker, less popular or less in charge in comparison to you?"…”
Section: Bullying Perpetrationmentioning
confidence: 99%
“…An 11-item self-report scale (Bjärehed, Thornberg, Wänström, & Gini, 2019) was used to measure bullying perpetration without using the word "bullying" to avoid the risks of under-reporting (i.e., social desirability bias based on the socially negative loading of the word) and misconception (i.e., incomplete, inaccurate or misleading personal conceptions of bullying). Instead of mentioning the word "bullying" and providing an a priori definition of bullying, the students were asked, "Think about the past three months: How often have you done the following things towards someone who is weaker, less popular or less in charge in comparison to you?"…”
Section: Bullying Perpetrationmentioning
confidence: 99%
“…Thornberg and Jungert (2014) found that bullying perpetration was linked to victim attribution (dehumanization and victim blaming merged into one factor after factor analysis) and moral justification in a sample of Swedish pre-adolescent students. These findings were then replicated in a recent study of direct bullying perpetration, while indirect bullying perpetration was only related to victim attribution (Bjärehed et al, 2020). In their study, Oliveira et al (2019) found that bullying behavior was associated with victim blaming, dehumanization, and displacement of responsibility.…”
Section: Social-cognitive Theory Of Moral Agencymentioning
confidence: 75%
“…Thornberg and Jungert (2014) found that bullying is related to attribution to victim and moral justification among moral disengagement mechanisms. Bjärehed, Thornberg, Wänström, and Gini (2020) studied the relationship between moral disengagement and direct and indirect bullying and pro-bullying behavior of students attending secondary school. They found that both direct and indirect bullying is related to moral legitimization, optimistic labeling, advantageous comparison, spreading responsibility, displacement of responsibility, and distorting results.…”
Section: Discussionmentioning
confidence: 99%